Modify the Chemical Composition of Jack Bean to be Used as Alternative Feedstuff in Poultry Diets - Utami , Sri; Rusmana, Denny; Wiradimadja, Rachmat; Rochana, Ana (International Journal of Poultry Science, 2018)
Background and Objective: Jack bean (Canavalia ensiformis L.) has the potential to be developed as a raw material in place of soybean meal for the manufacturing of poultry feed, but the presence of anti-nutritional compounds constitutes an obstacle to the utilization of jack bean as a raw material for poultry feed. This study analyzed the effects of different inoculum doses of Rhizopus oligosporus (R. oligosporus) and the fermentation time with the aim of increasing and decreasing the nutritional and anti-nutritional contents of jack bean, respectively. Materials and Methods: The main materials used in this study were jack beans and R. oligosporus. The experiment was conducted using a completely randomized design with a nested pattern (3×3) in triplicate. The treatment variables consisted of the R. oligosporus inoculum doses (0.1, 0.2 and 0.3%) and fermentation times (24, 48 and 72 h). The data were analyzed by analysis of variance and Duncan’s multiple-range differential test was used to determine the differences in the effects among the treatments. Results: This research showed that increase in the inoculum doses and fermentation times significantly increased the nutrient content, particularly the protein content and significantly decreased the anti-nutritional content (hydrocyanic acid, phytic acid and tannin) in jack beans. Conclusion: A fermentation process using a 0.2% (b/b) dose of R. oligosporus inoculum with a 72 h fermentation time yielded the best effects. This optimized process increased the nutritional content by more than 50%, decreased the anti-nutritional content by more than 50% and reduced the content of hydrocyanic acid and tannin by more than 75%.